Arboreal gems: resurrection of Isometrus sankeriensis Tikader & Bastawade, 1983 and descriptions of two new species of Isometrus Ehrenberg, 1828 (Scorpiones: Buthidae) from the Western Ghats, India - Sulakhe, Shauri; Deshpande, Shubhankar; Gowande, Gaurang; Dandekar, Nikhil; Ketkar, Makarand (European Journal of Taxonomy, 2022)
The Western Ghats of India is considered one of the richest biodiversity hotspots in the world. Documenting scorpion diversity has always been of paramount importance due to their species richness, ecological role and endemism, which calls for conservation priority. Scorpion diversity of the Western Ghats is probably underestimated given the ancestry of the group, and more field work in the region is very likely to uncover numerous undescribed taxa. Several new Indian species have recently been discovered in the scorpion genus Isometrus Ehrenberg, 1828 (Scorpiones: Buthidae). In this communication, we resurrect I. sankeriensis Tikader & Bastawade, 1983 and describe two new species from the Western Ghats of India, I. nakshatra sp. nov. and I. wayanadensis sp. nov., using an integrative taxonomic approach. In order to replace the lost holotype of I. sankeriensis, we designate a neotype and reassess the identity of this species. This work elevates the number of species of Isometrus found in India to eight and we expect many more scorpion discoveries from India with continued research.